(untitled) (Latakia University Journal -Engineering Sciences Series, 2024)
This research aims to analyze the total productivity (total output)/ (total input) and partial productivity (productivity of raw materials - productivity of capital - productivity of auxiliary services - productivity of machines - productivity of the work component or labor) of the manually operated plate bending machine and the plate bending machine that operates by hand. Powered. And comparing productivity, which is the result of (effectiveness: the degree of achieving goals, and efficiency: production at the lowest cost, least effort, and least waste of economic energies and resources, or (actual output) / (linear output), taking into account the time required to complete one tube, and the total expenses required to manufacture one tube, and the number of operators and workers required during both operations, The quality of the pipe - which is its suitability for use according to the standard specifications according to the concept of the International Organization for Standardization (ISO) - and so on. In order to evaluate productivity indicators. It also discusses the limitations of manual use, the importance of the process of bending plates with powered machines, the use of automation and technological innovations in the metal pipe industry and various modern local industries, and improving the quality of products in order to benefit humans and society.